Background Papers to Exposure Draft 24 on Current Cost Accounting (Book). - Burns, Thomas J.; Chandra, Gyan (The Accounting Review, 1980)
Reviews the book "Background Papers to Exposure Draft 24 on Current Cost Accounting."